We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
324
1
avatar+164 

2x (3 - x)

 

it it would be 2x * 3 = 6x then 2x * -x Is that right? If so what is the answer?

 Oct 28, 2017
 #1
avatar+7601 
0

2x( 3 - x )

 

=   2x * 3   +   2x * -x

 

=   2 * 3 * x   +   2 * x * x * -1

 

=   6x   +   - 2x2

 

=   6x - 2x2

 Oct 28, 2017

19 Online Users

avatar
avatar